2022
DOI: 10.1177/13623613221105836
|View full text |Cite
|
Sign up to set email alerts
|

Leisure, employment, community participation and quality of life in caregivers of autistic children: A scoping review

Abstract: Parenting an autistic child can reduce the time parents have to participate in their own interests, but the impact this has on caregiver quality of life is not well understood. The aim in undertaking this scoping review was to examine and describe current research about occupational participation and quality of life among parents of autistic children. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension guidelines, a comprehensive search of multiple databases was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 105 publications
5
27
1
1
Order By: Relevance
“…Several meaningful activities were identified by parents with the most common being employment, family outings, and leisure activities. Past literature has also highlighted similar activities as being beneficial for QoL in caregivers of children with additional needs, including autism (Davy et al, 2022 ), with increased frequency of health-related activities associated with higher levels of maternal QoL (Bourke-Taylor et al, 2012 ; Harris et al, 2022 ). However, other research has found that increased participation in leisure and community activities resulted in poorer physical health-related QoL in mothers of autistic children (Rizk et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several meaningful activities were identified by parents with the most common being employment, family outings, and leisure activities. Past literature has also highlighted similar activities as being beneficial for QoL in caregivers of children with additional needs, including autism (Davy et al, 2022 ), with increased frequency of health-related activities associated with higher levels of maternal QoL (Bourke-Taylor et al, 2012 ; Harris et al, 2022 ). However, other research has found that increased participation in leisure and community activities resulted in poorer physical health-related QoL in mothers of autistic children (Rizk et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…All caregivers interviewed in the current study were primary caregiving mothers. Although prior research demonstrates reduced QoL in mothers of autistic children compared to fathers (McStay et al, 2014b ), the role of participation on QoL in fathers and/or secondary caregivers remains relatively unknown (Davy et al, 2022 ). Therefore, further investigation into the occupational experiences of both primary and secondary caregivers of autistic children would help to improve our understanding of how best to support both parents of autistic children in achieving good QoL.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of caregiver well‐being in raising autistic children is well established, particularly given the additional stressors that many caregivers experience. For example, caregivers of autistic children have higher demands placed on them related to caring for their autistic children including attending additional health professional appointments (Davy et al, 2022; DePape & Lindsay, 2015). Davy et al (2022) highlighted the impact on caregivers' quality of life, which influenced their own social participation levels for leisure, community access and employment.…”
Section: Introductionmentioning
confidence: 99%